Uncertainty modeling in knowledge engineering and decision making : proceedings of the 10th International FLINS Conference, Istanbul, Turkey, 26-29 August 2012 - Kahraman, Cengiz; Kerre, Etienne E.; Bozbura, Faik Tunc (World Scientific proceedings series on computer engineering and information science ;, 2012)
FLINS, originally an acronym for Fuzzy Logic and Intelligent Technologies in Nuclear Science, is now extended to Computational Intelligence for applied research. The contributions to the 10th of FLINS conference cover state-of-the-art research, development, and technology for computational intelligence systems, both from the foundations and the applications points-of-view.